The construction of reinforced concrete slab at Riana South Condominium / Qamarul Azarin Rusli - Rusli, Qamarul Azarin (Universiti Teknologi MARA, Perak, 2018)
Building construction is the process of constructing a building or an infrastructure. Slab is a structural element that is made of concrete and is used to create flat horizontal surfaces such as floors, roof decks and ceilings. Hence, this report will discuss about the method of constructing reinforced concrete slab. This report was conducted for the building construction and construction of reinforced concrete slab at Riana South, Cheras, Kuala Lumpur. The prime objective of building construction is to make sure that the performance of the building can be continues to the utmost throughout its design life. The method of study used for this report were interviews, case study and literature reviews. The objectives of the report are to identify the method of constructing reinforced concrete slab on a high rise building, to determine the problems occurred and solutions taken to solve problems throughout the slab. To conclude, as slabs are the foundation for most construction, it is extremely important to understand all aspects of development to completion.